Preparation of Polyvinylidene Fluoride Nano-Filtration Membranes Modified with Functionalized Graphene Oxide for Textile Dye Removal - Hirra Ahmad; Muhammad Zahid; Zulfiqar Ahmad Rehan; Anum Rashid; Saba Akram; Meshari M. H. Aljohani; Syed Khalid Mustafa; Tayyaba Khalid; Nader R. Abdelsalam; Rehab Y. Ghareeb; Mohammad S. AL-Harbi (Membranes, 2022)
Water scarcity has become one of the most significant problems globally. Membrane technology has gained considerable attention in water treatment technologies. Polymeric nanocomposite membranes are based on several properties, with enhanced water flux, high hydrophilicity and anti-biofouling behavior, improving the membrane performance, flexibility, cost-effectiveness and excellent separation properties. In this study, aminated graphene oxide (NH2-GO)-based PVDF membranes were fabricated using a phase-inversion method for textile dye removal. These fabricated membranes showed the highest water flux at about 170.2 (J/L.h−1.m−2) and 98.2% BSA rejection. Moreover, these membranes removed about 96.6% and 88.5% of methylene blue and methyl orange, respectively. Aminated graphene oxide-based polyvinylidene fluoride (PVDF) membranes emerge as a good membrane material that enhances the membrane performance.